The use of theory of constraints to improve production efficiency - industrial practice and research results - Trojanowska, J. (2017)
The production activity of companies is dependent on both internal and external conditions in which they operate. Dynamically changing market requirements force companies to use different methods and management tools in order to improve their competitive position on the market. Today, business executives often decide to use the tools offered by the Theory of Constraints. In this paper the authors describe the theory of constraints and analyze the impact of application of this methodology on selected measures of production efficiency. Some industrial case studies are presented and obtained results, concerning application of theory of constraints, are discussed. Also some particularities, related with practical application of this methodology, are highlighted.